Analisis Pemasangan Filter Pasif Single Tuned Untuk Mereduksi Harmonisa Pada Motor Listrik Satu Phasa - Irawan, Andika; Zulfahri; Monice (Teknik Elektro Universitas Lancang Kuning, 2024)
The use of a non-linear load in the form of a single-phase electric motor results in the emergence of harmonics in the electric power system. In improving the quality of power that decreases due to harmonics, equipment that can reduce harmonics is used, namely a harmonic filter. Harmonic filters that are often used are single tuned passive filters. The purpose of this study is to recognize and examine the effect of using a single tuned passive filter to perform harmonic reduction and then to simulate the installation of a single tuned passive filter through the use of the Matlab program, by comparing the effect of a single tuned passive filter with lead on the global reference IEC 61000-3-2 Class D. The research method is a simulation, starting from collecting data, measuring harmonics, filter modeling, and estimating filter parameters. The assessment is carried out on devices that use single-phase electric motors. From this measurement obtained a value of Total Harmonics of voltage (THDv) and value of Total Harmonics of current (THDi. The reference load and filter are simulated using the Matlab program. The results show that: (1) Assembling a single tuned passive filter, can reduce THDi by 68, 24% and THDv of 0.95% for the load of the washing machine, as well as THDi of 79.22% and THDv of 0.99% for the load of the water pump, (2) Assembly of a single tuned passive filter can reduce harmonics from the 3rd order to the 29 in accordance with the IEC 61000-3-2 Class D tolak ukurd, (3) The single tuned passive filter gets a reduction in the current Individual Harmonic value (IHDi) which is 19.2% for the washing machine load and 46.62% for the water pump load. Keywords: Harmonics, Single Tuned Passive Filter, THDi, THDv